Triple Hierarchical Porous Carbon Spheres as Effective Cathodes for Li–O2 Batteries. Issue 4 (1st January 2019) - Jeong, Min-Gi; Kwak, Won-Jin; Islam, Mobinul; Park, Jiwon; Byon, Hye Ryung; Jang, Minchul; Sun, Yang-Kook; Jung, Hun-Gi
Abstract : This paper presents the synthesis and characterization of triple hierarchical porous carbon spheres as cathodes in lithium–oxygen batteries. The porous carbon cathode exhibits a higher discharge capacity and average discharge potential compared to a typical carbon black cathode. This superior electrochemical result can be attributed to the triple hierarchical pores of the cathode: micropores that act as channels for oxygen to flow without interruption by the accumulated discharge product, abundant mesopores that shape the size of the discharge product and transport the electrolyte, and macropores that easily accommodate the accumulation of discharge product. To further promote Li2 O2 formation/decomposition, the cathode can be decorated with a Ru catalyst, which strongly influences the oxygen evolution reaction performance. Conspicuously, triple hierarchical porous carbon spheres exhibit a homogeneous distribution of the Ru catalyst and thus provide an appropriate architecture. The synergistic effect from the unique structure and catalytic competence of Ru increases the capacity and rate capability with lower over-potential, and facilitates the formation of Li2 O2 . This can be decomposed at a low potential during recharge and thus contributes to the very high energy efficiency.